2013
DOI: 10.1111/are.12148
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival and growth performances with stocking density manipulation and shelter availability in bagrid catfishMystus nemurus(Cuvier & Valenciennes 1840) larvae

Abstract: Manipulation of stocking densities (10, 20, 30, 40 and 50 larvae L À1 ), each with or without the presence of shelter was conducted to determine the effects on survival, cannibalism and growth performances of larval bagrid catfish Mystus nemurus (Valenciennes 1840) from 2 to 14 days after hatching. This study revealed that stocking density significantly affected survival, cannibalism, total length, feed intake, specific growth rate and final weight of bagrid catfish larvae. Significantly higher survival was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…Similar negative phototactic behaviour has also been reported in other catfish species (e.g. Heterobranchus longifilis : Kerdchuen & Legendre, ; Clarias gariepinus : Britz & Pienaar, ; Silurus glanis : Kozlowski & Poczyczynski, ; Mystus nemurus : Rahmah et al, ; Lophiosilurus alexandri : Kitagawa et al, ; Hatcheria macraei : Barriga, Espinos, Walter, & Miguel, ). Moreover, their elongated body shape along with flattened head having subterminal mouth and a prognathic upper lip, barbels and very small dorsal eyes enable them like other catfishes to use tactile techniques rather than visual sense for feeding (Alexander, ; Hardy, Steinworth, & Hale, ).…”
Section: Discussionsupporting
confidence: 76%
“…Similar negative phototactic behaviour has also been reported in other catfish species (e.g. Heterobranchus longifilis : Kerdchuen & Legendre, ; Clarias gariepinus : Britz & Pienaar, ; Silurus glanis : Kozlowski & Poczyczynski, ; Mystus nemurus : Rahmah et al, ; Lophiosilurus alexandri : Kitagawa et al, ; Hatcheria macraei : Barriga, Espinos, Walter, & Miguel, ). Moreover, their elongated body shape along with flattened head having subterminal mouth and a prognathic upper lip, barbels and very small dorsal eyes enable them like other catfishes to use tactile techniques rather than visual sense for feeding (Alexander, ; Hardy, Steinworth, & Hale, ).…”
Section: Discussionsupporting
confidence: 76%
“…), but not in juvenile Asian redtail catfish Hemibargus nemurus (Bagridae) (Rahmah et al . ). The function of shelter as light refuge in nocturnal sharptooth catfish has also been indicated, as growth in constantly lit tanks was enhanced with the addition of shelter, while no effect was observed in constantly dark tanks (Britz and Pienaar ).…”
Section: Effects Of Structural Enrichmentmentioning
confidence: 97%
“…The differing results could depend on the fact that shelter structures where different between the studies (entangled plastic strips in the former, half PVC cylinders in the latter), as well as number of fish, experimental time and rearing environment. Shelter structures (plastic mesh materials) reduced cannibalism in African sharptooth catfish Clarias gariepinus (Clariidae) (Hecht and Appelbaum 1988;Hossain et al 1998), but not in juvenile Asian redtail catfish Hemibargus nemurus (Bagridae) (Rahmah et al 2013). The function of shelter as light refuge in nocturnal sharptooth catfish has also been indicated, as growth in constantly lit tanks was enhanced with the addition of shelter, while no effect was observed in constantly dark tanks (Britz and Pienaar 1992).…”
Section: Structures As Sheltersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the present study indicated that B. sinensis fry reared using PVC pipes and concrete bricks for shelters showed higher SGR and CF than those reared without shelters. Based on the different behaviors of fish, certain types of shelters are species‐specific (Rahmah et al., ). Some salmonids prefer rocks rather than sand substrates, because they can hide between the rocks and reduce daytime energy expenditure (Suttle et al., ), while the mud eel Monopterus cuchia prefers water hyacinth ( Eichhornia crassipes ) compared to PVC pipes and mud as shelters (Narejo et al., ).…”
Section: Discussionmentioning
confidence: 99%